EVALUASI PRAKTEK PENDIDIKAN ANAK USIA DINI DITINJAU DARI TEORI DEVELOPMENTALLY APPROPRIATE PRACTICE - H Utsman (Jurusan Pendidikan Masyarakat Fakultas Keguruan Ilmu Pendidikan Universitas Siliwangi, 2017)
Abstract: The application of early childhood education appropriate to the child's development is very important, because inaccuracies will have a negative impact perkebangan next child. Therefore research in order to know: 1) Practice proper education and improper in early childhood education at some kindergartens in terms of the theory of Developmentally Appropriate Practice. 2) The learning process is carried out by teachers in some kindergartens, 3) Characteristics of early childhood and its implications for learning in kindergarten bebeapa. This study used a qualitative approach and data were collected through interviews and field observations. Data were analyzed with constant comparative. The result is: 1) The teachers have done ragsangan experience needed to encourage the children and learning activities appropriately. Likewise, the social development of emotional guidance by means of modeling and encouragement so that children dare to do what is good and right. While planning a less precise because the teachers do just do one aspect only, 2) The process of learning is done early childhood teachers to basically play while learning. Besides, the study also made to the development and improvement of the potential of the child, 3) Most teachers understand the characteristics of the students, and on the basis of the characteristics of teachers design and implement learning activities appropriate child development. Keywords: Education of children; Developmentally Appropriate Practice